Río Iguazú Superior: química del agua y comentarios biológicos sobre alguno de sus peces - Gómez, Sergio Enrique (2009)
During the periods 1982-1986 and 2004-2007 intense campaigns of ichthyic research were conducted in the upper portion of the Iguazú River in the Argentinean province of Misiones. Water samples were collected from Andresito and Yacutinga (25º33´S; 54º04´W) to the Iguazú waterfalls in the Iguazú National Park (25°31′ S, 54°8′ W). In addition, some local streams (Uruzú and Urugua-í) were sampled. Our chemistry data analysis and biological observations showed little modifications in general conditions in the past 20 years, except for an increment in water conductivity and alkalinity and a decrease in water hardness. The upper portion of the Iguazú River can be considered oligotrophic and oligohaline with soft water and a low number of fish species, most of them endemic. Three exotic species were recorded, probably coming from nearby Brazilian dams. We propose that the low species number and the high number of endemisms are the result of the combination of effective zoogeographic barriers, the size of the basin and the oligotrophy of the system. Mayor threats for this basin are the destruction of the subtropical rainforest, the anthropic alterations of the river natural flow, a probable salinization process and the introduction of exotic and border species in protected areas.